EFEKTIVITAS HUKUM ADAT SASI DALAM PELESTARIAN SUMBER DAYA ALAM PADA MASYARAKAT AMBON: The Effectiveness of Sasi Customary Law in Preserving Natural Resources in the Ambon Community - Alfons Vindy; Aryo Subroto (Dialogia Iuridica, 2024)
This research aims to examine and analyze the regulation of Sasi customary law and the effectiveness of Sasi law in the right to conserve natural resources in Ambon society. This research is conducted using empirical legal research method. The results of the study show that Sasi customary law plays an important role in the conservation of natural resources of the Ambon community. Sasi customary law provides general guidelines on human behavior, establishes women's rights, prevents crime, distributes natural resources fairly, and determines how to manage natural resources at sea and on land.This research is also to determine the effectiveness of sasi customary law in saving the natural resources of the Ambon community, and that sasi customary law is able to be applied amidst social, economic and environmental changes in natural resource management, and researchers also examine the obstacles and challenges of implementing sasi customary law and evaluate the role of government and related stakeholders ini supporting natural resource conservation. Based on data analysis, there is a gap between the application of Sasi customary law and the real need to preserve environmental functions. As a recommendation, efforts are needed to create synergy between Sasi customary law and  regulation which applies, like Basic Agrarian Law, for ensure conservation sustainability and can provide insight into customary law which ca contribute to the conservation of natural resources. Strengthening the Ambon community's understanding and awareness of the importance of Sasi customary law is also key to improving its effectiveness.